2010
DOI: 10.1161/circresaha.110.226613
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of Neutral Cholesterol Ester Hydrolase 1 in Cholesterol Removal From Human Macrophages

Abstract: Rationale: Hydrolysis of intracellular cholesterol ester (CE) is the key step in the reverse cholesterol transport in macrophage foam cells. We have recently shown that neutral cholesterol ester hydrolase (Nceh)1 and hormone-sensitive lipase (Lipe) are key regulators of this process in mouse macrophages. However, it remains unknown which enzyme is critical in human macrophages and atherosclerosis.Objective: We aimed to identify the enzyme responsible for the CE hydrolysis in human macrophages and to determine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 54 publications
4
78
1
Order By: Relevance
“…3B ). Recent fi ndings show that NCEH1 is the enzyme primarily involved in the hydrolysis of CE in human macrophages, and the contribution of CES1 is lower ( 45 ). Future experiments should address the differences in the activity of the specifi c CE hydrolases between monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…3B ). Recent fi ndings show that NCEH1 is the enzyme primarily involved in the hydrolysis of CE in human macrophages, and the contribution of CES1 is lower ( 45 ). Future experiments should address the differences in the activity of the specifi c CE hydrolases between monocytes and macrophages.…”
Section: Discussionmentioning
confidence: 98%
“…C D E because 76-0079, a LIPE inhibitor, which is used to inhibit LIPE in PNPLA2-deficient adipocyes, also inhibits p-nitrophenyl butyrate (PNPB) hydrolase activity of human CES1 39) . The role of CES1 in lipolysis was further supported by the significantly positive correlation of its expression with cytosolic TG lipase activities in the subcutaneous and mesenteric fat ( Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently reported that disruption of Nceh1 promotes the formation of foam cells and accelerates the development of atherosclerosis in mice lacking either Apoe or LDL receptor ( Ldlr ) ( 9 ). In humans, NCEH1 plays a more critical role in cholesterol removal from monocyte-derived macrophages ( 10 ). Ultimately, however, accumulating evidence has suggested that reverse cholesterol transport is only one of a number of diverse functions of macrophages in atherogenesis ( 11 ).…”
Section: Measurements Of Oxysterolsmentioning
confidence: 99%